The external knowledge sourcing process in multinational corporations. (9th February 2016) - Monteiro, Felipe; Birkinshaw, Julian
Abstract : Research summary: We study the processes through which multinational corporations (MNCs) identify and make use of external sources of knowledge. Based on a seven‐year longitudinal study of one MNC's overseas scouting unit, we show how a simple one‐directional "channelling" process gradually gave way to three higher value‐added processes, labelled "translating, " "matchmaking, " and "transforming." Building on these insights, we develop an integrative framework, defining the conditions under which each of the four processes is likely to transpire, and showing how the stock of social capital held by the scouting unit allows it to perform increasingly high value‐added activities over time. Implications for the MNC, external knowledge sourcing, and boundary‐spanning literatures are discussed . Managerial summary: Over the years, many multinational corporations (MNCs) have created overseas "scouting" units to tap into new ideas and opportunities in leading‐edge markets, but with mixed outcomes. In this study, we describe the development of a European telecom firm's scouting unit in Silicon Valley during the 2000s, focusing on the specific approaches used by the scouting managers to build effective connections between Silicon Valley start‐ups and the firm's business units back in Europe. We identify four distinct approaches for different types of opportunities, and we observe a clear sequencing of effort over time as the scouting managers built the necessary capabilities and credibility . Copyright © 2015 John Wiley & Sons, Ltd.